2021
DOI: 10.1007/s10072-021-05231-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and behavioral manifestations in SARS-CoV-2 infection: not specific or distinctive features?

Abstract: Patients with COVID-19 are increasingly reported to suffer from a wide range of neurological complications, affecting both the central and peripheral nervous system. Among central manifestations, cognitive and behavioral symptoms are to date not exhaustively detailed. Furthermore, it is not clear whether these represent a combination of non-specific complications of a severe systemic disease, not differing from those usually seen in patients suffering from heterogenous pathological conditions affecting the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 79 publications
(92 reference statements)
2
5
0
1
Order By: Relevance
“…Thirty percent of patients with COVID-19 have a pathological score compared to none in the control group. These findings are in agreement with previous studies showing an impairment in working memory abilities in COVID+ patient ( Almeria et al, 2020 ; Graham et al, 2021 ; Jaywant et al, 2021 ; Negrini et al, 2021 ; Stracciari et al, 2021 ). Again, this data may be due to the neuroinvasive nature of the virus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thirty percent of patients with COVID-19 have a pathological score compared to none in the control group. These findings are in agreement with previous studies showing an impairment in working memory abilities in COVID+ patient ( Almeria et al, 2020 ; Graham et al, 2021 ; Jaywant et al, 2021 ; Negrini et al, 2021 ; Stracciari et al, 2021 ). Again, this data may be due to the neuroinvasive nature of the virus.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the number of people with at least one pathological score was higher in patients with SARS-CoV-2 infection than in controls. These findings reflect previous research showing cognitive deficits in COVID-19 patients such as impairments in memory ( Almeria et al, 2020 ; Woo et al, 2020 ; Alemanno et al, 2021 ; Jaywant et al, 2021 ; Negrini et al, 2021 ; Stracciari et al, 2021 ; Yesilkaya et al, 2021 ), executive functions ( Almeria et al, 2020 ; Alemanno et al, 2021 ; Beaud et al, 2021 ; Jaywant et al, 2021 ; Negrini et al, 2021 ; Stracciari et al, 2021 ; Yesilkaya et al, 2021 ), attention ( Almeria et al, 2020 ; Woo et al, 2020 ; Graham et al, 2021 ; Jaywant et al, 2021 ; Negrini et al, 2021 ; Stracciari et al, 2021 ; Yesilkaya et al, 2021 ), and working memory ( Almeria et al, 2020 ; Graham et al, 2021 ; Jaywant et al, 2021 ; Negrini et al, 2021 ; Stracciari et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, it is mandatory to control for such intervening variables in order to provide valid data on the cognitive profile of COVID-19-recovered individuals. It is indeed still a matter of debate whether the cognitive toll of COVID-19 actually reflects the neurological effects of SARS-CoV-2 infection or is confounded by predisposing risk factors [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Вероятно, механизмы развития когнитивных и нейропсихиатрических симптомов при инфекции SARS-CoV-2 носят вторичный характер -как проявление гипоксии, воспаления, лихорадки и побочных эффектов лекарственных препаратов. Наиболее универсальной манифестацией тяжелой инфекции, развивающейся у каждого десятого пациента во время госпитализации (чаще у пожилых и лиц с КН), является делирий [42].…”
Section: клиническая картина методы обследования и лечение при основн...unclassified